Newton's Method for the Matrix Nonsingular Square Root. (31st August 2014) - Li, Chun-Mei; Shen, Shu-Qian
Abstract : Two new algorithms are proposed to compute the nonsingular square root of a matrix A . Convergence theorems and stability analysis for these new algorithms are given. Numerical results show that these new algorithms are feasible and effective.